Ground Beetles in a Changing World: Communities in a Modified Wetland Landscape - Nanni, Analía Soledad (2019)
Wetlands are being increasingly affected by anthropogenic activities worldwide. The Lower Delta of the Paraná River, one of the most important wetlands in Argentina, has been profoundly altered because most of the natural environments were drained or diked to make them suitable for different agricultural activities. As a result, the landscape is characterized by a mosaic of Salicaceae afforestations of different ages interspersed with patches of secondary forests and grazing grasslands. The high susceptibility of Carabidae and Aphodiidae to natural and human-induced disturbances and management practices is reflected by changes in their spatiotemporal distribution. We performed a 1-year study to analyze and compare beetle’s communities inhabiting different habitat types in this modified wetland landscape. A total of 58 beetle species were recorded, of which 48 were carabids and 10 aphodids. Although species richness and diversity were higher in productive habitats (afforestations and grasslands) than in secondary forests, hydrophilic species were only found in the latter. Community parameters varied seasonally. Our results indicate a close relationship between wetland beetle communities and vegetation cover in each habitat type. Human activity increases heterogeneity across this landscape, which favors the colonization of new species but causes the loss or displacement of autochthonous species. The secondary forests could serve as alternative habitats for beetles typical of humid environments. We propose the maintenance of the current heterogeneous mosaic to favor the diversity of ground beetles and the implementation of changes in water management for the benefit of hydrophilic beetle species.